Anoctamin 1/TMEM16A in pruritoceptors is essential for Mas-related G protein receptor-dependent itch - Kim, Hyesu; Kim, Hyungsup; Cho, Hawon; Lee, Byeongjun; Lu, Huan-Jun; Kim, Kyungmin; Chung, Sooyoung; Shim, Won-Sik; Shin, Young Kee; Dong, Xinzhong; Wood, John N.; Oh, Uhtaek (Elsevier BV, 2022)
Itch is an unpleasant sensation that evokes a desire to scratch. Pathologic conditions such as allergy or atopic dermatitis produce severe itching sensation. Mas-related G protein receptors (Mrgprs) are receptors for many endogenous pruritogens. However, signaling pathways downstream to these receptors in dorsal root ganglion (DRG) neurons are not yet understood. We found that anoctamin 1 (ANO1), a Ca2+-activated chloride channel, is a transduction channel mediating Mrgpr-dependent itch signals. Genetic ablation of Ano1 in DRG neurons displayed a significant reduction in scratching behaviors in response to acute and chronic Mrgpr-dependent itch models and the epidermal hyperplasia induced by dry skin. In vivo Ca2+ imaging and electrophysiological recording revealed that chloroquine and other agonists of Mrgprs excited DRG neurons via ANO1. More importantly, the overexpression of Ano1 in DRG neurons of Ano1-deficient mice rescued the impaired itching observed in Ano1-deficient mice. These results demonstrate that ANO1 mediates the Mrgpr-dependent itch signaling in pruriceptors and provides clues to treating pathologic itch syndromes.